ORGANIZATION OF TEACHING MATHEMATICS IN PRIMARY CLASSES - I Fozilov Jakhongir Ibrokhimovich1; Abduraxmonova Mohinur Furqatjon qizi2; Topvoldiyeva Zuxraxon Ravshan qizi3 (American Journals, 2022)
This article discusses the concept of a lesson, its structure, the basic requirements for the lesson, types of lessons, some ways of organizing teaching mathematics to younger schoolchildren.
Keywords: Lesson,; content,; optimal teaching methods